Bimbingan Teknis Sistem Informasi Pengujian Sampel Balai Laboratorium Lingkungan, DLHK DIY - Fatkhiyah, Erfanti; Kusumaningsih, Rr. Yuliana Rachmawati; Ariyana, Renna Yanwastika (DHARMA BAKTI, 2021)
The Environmental Laboratory Office is one of the Technical Implementation Units under the Environment and Forestry Service of the Special Region of Yogyakarta, which is tasked with conducting sample testing including drinking water, waste water and surface water. Previous services were still manual, so to support services to consumers, an online information system for testing waste samples was developed. The information system developed is designed according to the existing flow in the Environmental Laboratory Office using the PHP Codeigniter framework to accelerate the customer service process, designed with a comfortable appearance for officers and consumers. Technical guidance is carried out to provide information and use of online information systems for staff or admins as well as consumers who test samples to the environmental laboratory office which is divided into two shifts, the first shift is for environmental laboratory staff which includes checking consumer data and test samples to producing results reports the test required by consumers, while the second shift is for consumers who will test the sample which includes account registration and test samples to the process of sending proof of payment.